2019
DOI: 10.18632/oncotarget.27235
|View full text |Cite
|
Sign up to set email alerts
|

ERO1α promotes hypoxic tumor progression and is associated with poor prognosis in pancreatic cancer

Abstract: Pancreatic cancer is a leading cause of mortality worldwide due to the difficulty of detecting early-stage disease and our poor understanding of the mediators that drive progression of hypoxic solid tumors. We therefore used a heavy isotope ‘pulse/trace’ proteomic approach to determine how hypoxia (Hx) alters pancreatic tumor expression of proteins that confer treatment resistance, promote metastasis, and suppress host immunity. Using this method, we identified that hypoxia stress stimulates pancreatic cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…In this study, we revealed that ERO1L expression is significantly elevated by activation of UPR. Consistent with two previous reports 35 , 36 , we also found that ERO1L can be induced by hypoxia, which is known to induce ER stress. The UPR-dependent elevation of ERO1L might be a reflection of the global enhancement of the entire secretory apparatus in response to ER stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we revealed that ERO1L expression is significantly elevated by activation of UPR. Consistent with two previous reports 35 , 36 , we also found that ERO1L can be induced by hypoxia, which is known to induce ER stress. The UPR-dependent elevation of ERO1L might be a reflection of the global enhancement of the entire secretory apparatus in response to ER stress.…”
Section: Discussionsupporting
confidence: 93%
“…ERO1L plays versatile oncogenic functions in human cancers, including rapid cell proliferation, increased cell invasion, promotion of angiogenesis, and immune escape 16 , 36 , 37 . Using the CRISPR/Cas9 approach, Gupta et al showed that ERO1L KO significantly suppresses PDAC cell proliferation and colony-forming potential 35 . Similarly, we found that shRNA-mediated ERO1L knockdown inhibits cell viability and colony-forming ability of two PDAC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proteome turnover analysis can be used to study disease states such as cancer and their potential treatments ( 67 , 68 , 69 , 70 , 71 , 72 , 73 ). One such study published by the Wiita lab examined proteome turnover in MM1.S multiple myeloma cells ( 72 ).…”
Section: Dynamic Silac Approachesmentioning
confidence: 99%
“…This low availability of oxygen is a condition derived from the rapid growth and accumulation of cells within the tumour. Inside the malignant growing tissue, cells undergo an adaptation to hypoxia and are able to grow with a resultant expansion of the tumour (Gupta et al., 2019). Activated PSC that are included in the tumour mass will also be subjected to hypoxia.…”
Section: Introductionmentioning
confidence: 99%